Скарб знарядь для обробітку ґрунту з Чорнівського археологічного комплексу - Ільків, Микола; Ilkiv, Mykola; Рідуш, Богдан; Ridush, Bogdan; Gorbanenko, Sergiy; Горбаненко, Сергій (In Sclavenia terra, 2022)
On the territory of the Chornivka archaeological complex the Bukovynian expedition of the State Enterprise «Science Research Centre “Protective Archaeology Service of Ukraine”» of the Institute of Archaeology of the National Academy of Sciences of Ukraine monitors the condition of the monument sites. Thanks to this, in 2022, a deposit of parts for the instruments for soil cultivation was discovered outside the boundaries of known settlements. Two gouters, two tusks and a bushing hoe were found. The publication is dedicated to introducing this hoard into scientific circulation. The find of a deposit of agricultural tools outside the archaeological sites confirms the importance of constant monitoring of both the sites and the areas around them. A comparative analysis of these details with materials of the Raykovetska monuments also confirms the chronology of the hoard’s laying — VIII—X centuries. The find of both sets in pairs (2 gouters and 2 tusks) proves that they were intended for use on ploughable tools / ploughs. The comparative analysis against the background of similar findings of the last quarter of the 1st millennium AD on the territory of the south of Eastern Europe in various archaeological cultures proves the highest level of development of these tools for primary soil tillage for its time. Today, out of five locations of such foundations, three were discovered in a small part of the area of the Raykovetska culture in the northern part of Bukovyna. Do these finds testify to the better study of the Raykovetska sites in the Chernivtsi region compared to others or are a feature of this micro-region of settlement of the chronicled Slavs — time will tell. The deposition of the material was probably of a purely domestic nature — short-term storage of property; the contents of the deposit emphasize the importance of agriculture for ancient people. Detailing the interpretation of such material (not precious) deposits requires the creation of a catalog for Eastern Europe as complete as possible.
Keywords: Early Slavs, Raykovetska culture, deposit, agricultural tools, gouter, tusk, hoe